Hydropulse drive of the installation for vibrating dehydration of by-products of food industry enterprises - Iskovych-Lototskyi, R. D.; Obertiukh, R. R.; Polishchuk, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Analysis of pressure change impact in accumulated volume of hydropulse drive on non uniformity of its electromechanical part operation is carried out, the expediency of fly-wheel installation on the shaft of electric motor drive to provide the operation of the latter with preset non uniformity factor is substantiated. The calculation technique described can be used for calculation hydrodrives with known regularities of load changes on the main shaft of their electromechanical part.